Preparation method and application of water-resistant electrolyte for sodium-ion battery
By using sodium salts, organic solvents and ester additives in sodium ion batteries, the problem of insufficient water resistance of existing electrolytes is solved, the cycle stability and rate performance of the battery are significantly improved, the manufacturing cost is reduced, and the industrialization of sodium ion batteries is provided.
Patent Information
- Application Number
- CN202510412541.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-05-02
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing sodium ion battery electrolyte has insufficient water resistance, resulting in a decline in battery performance in high humidity environments, increasing the drying cost of industrial production.
A water-resistant electrolyte is prepared by combining sodium salt, mixed organic solvents and ester film formation and auxiliary additives. By optimizing the electrode/electrolyte interface, a stable electrolyte membrane is formed to improve the stability and water resistance of the battery.
It significantly improves the cycle stability and rate performance of sodium ion batteries, can work stably in high-voltage and high humidity environments, reduces the manufacturing cost of batteries, and provides a feasible solution for the industrialization of sodium ion batteries.
Smart Images

Figure CN119920981A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a preparation method and application of a water-resistant electrolyte for sodium ion batteries. Background Art
[0002] With the rapid growth of the lithium-ion batteries (LIBs) market, the limited lithium resources have attracted people's attention. Rechargeable sodium-ion batteries (SIBs) are a promising energy storage technology due to their abundant reserves and low redox potential (-2.71 V compared with standard hydrogen electrode).
[0003] Sodium-ion batteries are also composed of key materials such as positive electrode, negative electrode, electrolyte, and separator. Today's sodium-ion positive electrode materials include layered transition metal oxides, polyanion-based materials, Prussian blue analogs (PBAs), and organic materials. Among them, PBAs are beneficial to Na+ due to their unique open framework structure and large interstitial space. + In addition, compared with lithium iron phosphate (LiFePO4) in LIBs, PBAs have similar energy density, easy synthesis process, cheap raw materials and low manufacturing cost (no high temperature calcination required), making PBAs one of the most promising cathodes for large-scale commercial production of SIBs. The industrialization of Prussian blue sodium-ion batteries has strict requirements on environmental humidity. The water resistance of the electrolyte has the potential to reduce the production equipment requirements and the manufacturing cost of the battery, and can solve the construction cost of expensive drying rooms. Adjusting the electrolyte additives to achieve the desired effect is also the most commonly used method in the battery industry and the most cost-saving method. This approach encourages further exploration of innovative electrolytes with unique physical and chemical properties, providing a promising direction for future high-energy and low-cost sodium-ion batteries. Summary of the invention
[0004] In order to solve the problems and shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a water-resistant electrolyte for a sodium ion battery, based on reducing resource consumption, combined with the development trend of new electrolytes, and committed to improving the cycle stability of sodium ion batteries and the problems faced by the industrial drying cost of sodium ion batteries.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing a water-resistant electrolyte for a sodium ion battery comprises a sodium salt, a mixed organic solvent and a combination of additives, wherein the combination of additives comprises a film-forming additive and an auxiliary additive, and the additives are all esters.
[0006] Further, the sodium salt includes any one or a combination of at least two of sodium perchlorate (NaClO4), sodium trifluoromethanesulfonate (NaOTf), sodium tetrafluoroborate (NaBF4), sodium difluorophosphate (NaPO2F2), sodium difluorooxalatoborate (NaDFOB), and sodium bis(oxalatoborate) (NaBOB).
[0007] Furthermore, the concentration of the sodium salt is 0.8~1.5 mol / L.
[0008] Furthermore, the solvent is at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC).
[0009] Furthermore, the film-forming additive is at least one of vinylene carbonate (VC), 1,3-propane sultone (PS), vinyl sulfite (ES), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), tripropargyl phosphate (TPP), and diethyl sulfate (DTD).
[0010] Furthermore, the mass percentage content of the film-forming additive in the electrolyte is 1% to 5%.
[0011] Furthermore, the auxiliary additive is at least one of tris(trimethylsilyl) borate (TMSB), trimethylsilyl trifluoromethanesulfonate (TMSOTf), and trimethylsilyl methane sulfonate (TMSOMs).
[0012] Furthermore, the mass percentage content of the auxiliary additive in the electrolyte is 0.5%~3%.
[0013] Furthermore, the preparation method is as follows: S1, in a glove box filled with argon atmosphere, the moisture and oxygen are less than 0.01 ppm, the sodium salt and the organic solvent are mixed in sequence, stirred thoroughly, and allowed to stand for 6 hours to obtain a clear and transparent pre-purified solution; S2, the additive is dissolved in the clear and transparent pre-purified solution obtained in step S1, and allowed to stand for 6 hours; S3, the molecular sieve is added to the pre-purified solution obtained in step S2, and allowed to stand for 6 hours, and finally the molecular sieve is removed to obtain a water-resistant electrolyte for a sodium ion battery.
[0014] Furthermore, the molecular sieve is a 3 Å or 4 Å molecular sieve.
[0015] The present invention also provides an application of a high-performance sodium ion battery water-resistant electrolyte in a sodium ion battery.
[0016] Furthermore, the high-performance sodium ion battery includes a positive electrode sheet, a separator, the water-resistant electrolyte described in the present invention, and a negative electrode sheet.
[0017] Furthermore, the positive electrode is Prussian blue (PB).
[0018] Furthermore, the separator is glass fiber and cellulose.
[0019] Furthermore, the negative electrode sheet is a sodium sheet (Na) and a hard carbon (HC).
[0020] The present invention is beneficial in that: The present invention selects and uses ester organic reagents as auxiliary additives for the electrolyte, which can significantly improve the performance of sodium ion batteries. The ester auxiliary additives can optimize the composition of the electrode / electrolyte interface, form a more stable SEI / CEI, and improve the stability of the battery. The optimized electrolyte can allow the battery to exist stably under high voltage, and the stability of the battery itself is improved, which significantly improves the safety performance of the battery. Reduce the side reactions of the battery under high voltage. Therefore, the electrolyte proposed by the present invention shows higher electrochemical stability, which can significantly improve the cycle and rate performance of the PB||Na button battery, and also shows excellent electrochemical stability in the PB||Na cylindrical battery. In particular, the electrolyte has a certain water resistance, and can still circulate stably after adding 500~1000 ppm of water, which can greatly reduce the drying cost required for the industrialization of Prussian blue sodium ion batteries, and provide a feasible solution for realizing the industrialization of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Comparison of the cycle performance and rate performance of HC||PB batteries assembled with the electrolytes of Example 1 and Comparative Example 1, Comparative Example 2, and Comparative Example 3 at 25°C, and comparison of the cycle performance and rate performance of PB||Na half-cells assembled with Experimental Example 1 and Comparative Example 1 at 25°C.
[0022] Figure 2 The Na||Na symmetric battery assembled in Experimental Example 1 and Comparative Example 1 at 0.5 mA cm -1 Cycling at current density.
[0023] Figure 3 Linear sweep voltammetry (LSV) of Experimental Example 1 and Comparative Example 1 and the current change curves of the PB||Na half-cell assembled in Experimental Example 1 and Comparative Example 1 under a continuous high voltage of 4.9V.
[0024] Figure 4 Cyclic voltammetry (CV) test and capacity loss characterization SEI dissolution test of the Cu||Na batteries assembled in Experimental Example 1 and Comparative Example 1 and capacity loss characterization SEI dissolution test of the Cu||Na batteries assembled in Experimental Example 1 and Comparative Example 1.
[0025] Figure 5PB||HC batteries assembled after adding 500 ppm and 1000 ppm of water to the electrolytes of Experimental Example 1 and Comparative Example 1, respectively.
[0026] Figure 6 This is the near infrared test after adding 0.5wt% water to the electrolyte of Experimental Example 1 and Comparative Example 1 respectively.
[0027] Figure 7 The cycling performance of the HC||PB cylindrical battery assembled with the electrolyte of Example 1 at room temperature. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0029] Abbreviations: Sodium perchlorate: NaClO4 Propylene carbonate: PC Dimethyl carbonate: DMC Vinyl carbonate: VC Fluorovinylene carbonate: FEC Tris(trimethylsilyl)borate: TMSB Trimethylsilyl trifluoromethanesulfonate: TMSOTf Example 1 The present embodiment provides a water-resistant electrolyte for sodium ion batteries, and the preparation method thereof comprises the following steps: adding 122.44 mg NaClO4, 1 mL of a mixed solvent of PC and DMC (mass ratio 7:3) to make the concentration thereof 1 mol / L, and then adding 1% of a film-forming additive VC accounting for 1% of the total mass of the electrolyte and 1% of an auxiliary additive TMSB accounting for 1% of the total mass of the electrolyte, to obtain the water-resistant electrolyte of the present invention.
[0030] Example 2 The electrolyte provided in this embodiment is different from that in Embodiment 1 in that the auxiliary additive is TMSOTf instead of TMSB.
[0031] Example 3 The electrolyte provided in this embodiment is different from that in Example 1 in that the film-forming additive is replaced by FEC instead of VC.
[0032] Comparative Example 1 This embodiment provides an electrolyte, and its preparation method includes the following steps: adding 122.44 mg NaClO4, 1 mL of a mixed solvent of PC and DMC (mass ratio 7:3) to make its concentration 1 mol / L, and then adding VC accounting for 1% of the total mass of the electrolyte.
[0033] Comparative Example 2 The electrolyte provided in this embodiment is different from that in Comparative Example 1 in that FEC is used instead of VC.
[0034] Comparative Example 3 The electrolyte provided in this embodiment is different from that in Comparative Example 2 in that TMSOTf accounts for 0.5% of the total mass of the electrolyte.
[0035] Figure 1 Comparison of the cycle performance and rate performance of the HC||PB battery assembled with the electrolytes of Example 1 and Comparative Example 1, Comparative Example 2, and Comparative Example 3 at 25°C, and comparison of the cycle performance and rate performance of the PB||Na half-cell assembled with the electrolytes of Experimental Example 1 and Comparative Example 1 at 25°C. Figure 1 It can be seen intuitively from the a part that after 100 cycles, the cycle retention rates of Experimental Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 are 94.12%, 88.34%, 73.19%, and 74.73%, respectively. Obviously, Experimental Example 1 has the best cycle stability. Figure 1 It can be seen from part b that there is no obvious difference between the four electrolytes at low rates. At current densities of 2 C and 3 C (1C=150 mAh / g), Experimental Example 1 can obviously exert more capacity and cycle stably, while Comparative Examples 2 and 3 can hardly exert capacity at high rates, indicating that the electrolyte of Experimental Example 1 has excellent rate performance. The experimental results show that in the full battery, Example 1 has the best cycle and rate performance, followed by Comparative Example 1. Therefore, the performance of Experimental Example 1 and Comparative Example 1 in various aspects will be further compared. Figure 1 Part c and part d are comparisons of the cycle performance and rate performance of the PB||Na half-cells assembled in Experimental Example 1 and Comparative Example 1, respectively. The experimental results show that the cycle and rate performance of Experimental Example 1 are superior to those of Comparative Example 1.
[0036] Figure 2 The Na||Na symmetric battery assembled in Experimental Example 1 and Comparative Example 1 at 0.5 mA cm -1 The experimental results show that compared with comparative example 1, experimental example 1 can maintain a stable cycle of 300 h, which is a huge improvement compared with comparative example 1 (67 h). At the same time, it can be seen from the enlarged box diagram that the polarization of experimental example 1 is greatly reduced, proving that the electrolyte of experimental example 1 has excellent chemical compatibility with Na.
[0037] Figure 3 Part a is the linear sweep voltammetry (LSV) of Experimental Example 1 and Comparative Example 1. Figure 3Part a shows that the electrochemical windows of Experimental Example 1 and Comparative Example 1 are basically the same, but it can be seen that the side reactions of Experimental Example 1 are reduced under high pressure.
[0038] Figure 3 Part b is the current change curve of Experimental Example 1 and Comparative Example 1 assembled PB||Na half-cells under a continuous high voltage of 4.9V. The figure shows that the leakage current of Experimental Example 1 is smaller under high voltage (1.34 vs. 1.12), which confirms that the side reaction of LSV test Experimental Example 1 is reduced under high voltage.
[0039] Figure 4 Part a is the cyclic voltammetry (CV) test and capacity loss characterization SEI dissolution test of the Cu||Na battery assembled in Experimental Example 1 and Comparative Example 1. Figure 4 In part a, it can be seen that the broad reduction peak at 0~0.5 belongs to the decomposition peak of the electrolyte solvent, and the peak between 2.5~3.0 is the oxidation peak of the solvent. The first circle shows that after adding TMSB, the decomposition of the electrolyte is greatly reduced, and the second and third circle curves are almost identical, indicating that one circle of activation in Experimental Example 1 can form a stable solid electrolyte membrane, and the decomposition of the electrolyte is greatly reduced.
[0040] Figure 4 The figure shows the SEI dissolution test for the capacity loss of the Cu||Na batteries assembled in Experimental Example 1 and Comparative Example 1. The increase in capacity after each pause clearly shows that a reduction reaction of electrolyte decomposition occurs at the anode to compensate for the dissolution of the SEI that has been formed during the long open circuit pause. After 50 h of storage, the capacity of Experimental Example 1 increased by 1.6 μAh, and that of Comparative Example 1 increased by 9.7 μAh, which is 6.06 times that of Experimental Example 1. In addition, the experiment was conducted on a low-surface-area, dense copper electrode. Since the hard carbon (HC) anode has more exposed surface pores, the actual SEI dissolution is expected to be much more serious. After 5 h of storage, the capacity loss of Comparative Example 1 was 0.7 μAh, while there was no capacity loss in Experimental Example 1. The dissolution of SEI in Experimental Example 1 was greatly suppressed by the lowest capacity loss and the most stable long-cycle battery performance evaluation. This shows that the additive helps to generate a stable SEI with lower solubility, which is consistent with the CV test results.
[0041] Figure 5The PB||HC battery assembled after adding 500 ppm and 1000 ppm of water to the electrolyte of Experimental Example 1 and Comparative Example 1, respectively. After adding 500 ppm and 1000 ppm, 91.29% and 90.80% of the capacity remained after 100 cycles at 1 C, respectively, proving that the addition of water has almost no effect on the cycle stability of the battery. After adding 500 ppm and 1000 ppm to Comparative Example 1, the capacity dropped rapidly after 100 cycles, and 82.77% and 72.21% of the capacity remained, respectively, and a stable cycle could not be maintained, indicating that the electrolyte has water resistance after adding TMSB. In addition, after adding water to the electrolyte of Experimental Example 1, the initial cycle capacity decreased slightly, while the capacity of Comparative Example 1 decreased significantly. It is speculated that the TMSB in the electrolyte of Experimental Example 1 absorbed part of the water, and a small part was absorbed by the PB electrode, resulting in a slight decrease in capacity, while the water in the electrolyte of Comparative Example 1 was absorbed by the PB electrode, resulting in a significant decrease in capacity.
[0042] Figure 6 This is the near infrared test after adding 0.5wt% water to the electrolytes of Experimental Example 1 and Comparative Example 1. The peak of OH bond was detected in Comparative Example 1, but not in Experimental Example 1, indicating that TMSB in Experimental Example 1 absorbed part of the water, and the water in Comparative Example 1 could not be removed, which confirmed our above conjecture and proved that the electrolyte of Experimental Example 1 had certain water resistance.
[0043] Figure 7 Cycling performance of HC||PB cylindrical battery assembled with electrolyte of Example 1 at room temperature. The figure shows that the capacity retention rate of Comparative Example 1 after 100 cycles at 0.5C is only 83.89%, and the coulombic efficiency continues to decrease after 25 cycles. The capacity retention rate of Example 1 after 100 cycles at 0.5C in cylindrical battery is 92.29%, and it has ultra-high coulombic efficiency (≈100%). Experimental Example 1 shows excellent electrochemical stability and certain practical performance.
[0044] from Figures 1 to 7 It can be seen that the comprehensive performance of the electrolyte prepared in the embodiment is significantly better than that of the comparative example, especially its outstanding water resistance, which can reduce a lot of costs for the experiment; and it shows excellent performance in the HC||PB cylindrical battery, indicating that the high-performance water-resistant electrolyte of the invention has strong practical performance, which is conducive to reducing the manufacturing cost of Prussian blue sodium-ion batteries and promoting the commercialization process of sodium-ion batteries.
[0045] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A water-resistant electrolyte for sodium ion batteries, characterized in that: The invention comprises sodium salt, mixed organic solvent and combined additives, wherein the combined additives comprise film-forming additives and auxiliary additives, and both the film-forming additives and the auxiliary additives are esters.
2. The water-resistant electrolyte for sodium ion batteries according to claim 1, characterized in that: The sodium salt includes any one of sodium perchlorate (NaClO4), sodium trifluoromethanesulfonate (NaOTf), sodium tetrafluoroborate (NaBF4), sodium difluorophosphate (NaPO2F2), sodium difluorooxalatoborate (NaDFOB), and sodium bis(oxalatoborate) (NaBOB), or a combination of at least two thereof, and the concentration of the sodium salt is 0.8-1.5 mol / L.
3. The water-resistant electrolyte for sodium ion batteries according to claim 1, characterized in that: The solvent is any one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC), or a combination of at least two of them.
4. The water-resistant electrolyte for sodium ion batteries according to claim 1, characterized in that: The film-forming additive is at least one of vinylene carbonate (VC), 1,3-propane sultone (PS), vinyl sulfite (ES), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), tripropargyl phosphate (TPP), and diethyl sulfate (DTD).
5. The water-resistant electrolyte for sodium ion batteries according to claim 1, characterized in that: The mass percentage content of the film-forming additive in the electrolyte is 1%~5%.
6. The water-resistant electrolyte for sodium ion batteries according to claim 1, characterized in that: The auxiliary additive is at least one of tri(trimethylsilyl) borate (TMSB), trimethylsilyl trifluoromethanesulfonate (TMSOTf), and trimethylsilyl methane sulfonate (TMSOMs).
7. The water-resistant electrolyte for sodium ion batteries according to claim 1, characterized in that: The mass percentage content of the auxiliary additive in the electrolyte is 0.5%~3%.
8. A method for preparing a water-resistant electrolyte for a sodium ion battery according to any one of claims 1 to 7, characterized in that: The preparation method is as follows: S1, in a glove box filled with argon atmosphere, the water and oxygen are less than 0.01 ppm, the sodium salt and the organic solvent are mixed in sequence, fully stirred, and allowed to stand for 6 hours to obtain a clear and transparent pre-purified solution; S2, the additive is dissolved in the clear and transparent pre-purified solution obtained in step S1, and allowed to stand for 6 hours; S3, the molecular sieve is added to the pre-purified solution obtained in step S2, and allowed to stand for 6 hours, and finally the molecular sieve is removed to obtain the high-performance water-resistant electrolyte for the sodium ion battery.
9. The method for preparing a water-resistant electrolyte for a sodium ion battery according to claim 8, characterized in that: The molecular sieve is 3 Å or 4 Å molecular sieve.
10. Use of the water-resistant electrolyte according to any one of claims 1 to 7 in a sodium ion battery.
Citation Information
Patent Citations
Electrolytic solution and lithium ion battery containing same
CN112271338A
Sodium-ion battery electrolyte and sodium-ion battery
CN115799611A
Sodium-ion battery electrolyte, preparation method and sodium-ion battery
CN115954551A
Secondary battery and preparation method thereof, battery module, battery pack and electric device
CN116964767A
Sodium-ion battery electrolyte and sodium-ion battery
CN117497846A